Pengaruh Kompetensi dan Motivasi terhadap Kinerja Pengelolaan Keuangan Daerah - Ida Rosnidah; Mohamad Taufik Hidayat; Iim Rohimatun Nahdiyyah (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
ABSTRACTThe performance of Regional Financial Management at the Regional Secretariat of Cirebon City is still low. This can be seen from the indications that not all employees understand the operation of basic government accounting computer programs related to the implementation of their work, this is due to lack of competence and motivation to complete tasks. The purpose of this study was to obtain empirical evidence of the influence of competence and motivation on the performance of regional financial management. The method used in this study is a survey method with data collection techniques through questionnaires. The research population is all employees at the Regional Secretariat of Cirebon City with random sampling. Data analysis using multiple regression. The results showed that the competence and motivation of employees at the Regional Secretariat of Cirebon City was not optimal. Both competence and motivation have a large effect on the performance of regional financial management, partially, but if competence and motivation are carried out together, the influence will increase on the performance of regional financial management. The novelty of this research is the object of research conducted in public sector.Keywords: Competence; motivation; performance of regional financial management